Bioethanol From Oil Palm Empty Fruit Bunch (OPEFB): a Review Pretreatment and Enzymatic Hydrolysis - Irwan Irwan; Salim Agus (IAIN Kendari, 2021)
The fossil fuel crisis will remain a major topic that needs to be looked for a solution together until other alternative fuels are found. Bioethanol has now become a trend and focus of researchers in Indonesia and various parts of the world as an environmentally friendly alternative energy and given the potential of Indonesia as one of the largest palm oil-producing countries in the world with the amount of lignocellulosic biomass waste such as Oil Palm Empty Fruit Bunch (OPEFB). OPFEB is the most desirable and realistic alternative to substitute fossil fuels as the main energy source. The use of these wastes as renewable fuels is very significant in terms of expanding economic value and solving environmental problems. This review paper offers an insight into the current creative approaches to the development of OPEFB such as characteristics of OPEFB, pretreatment process, and enzymatic hydrolysis.